Analisis Deskriptif Kemampuan Meniru Gerak Senam Ritmik Peserta Didik melalui Aplikasi Just Dance Now di SDN Bulay 1 Pamekasan - Yoyok Yulianto; Moh.Hosnan Arisandi; Achmad Mujahid Afifuddin; Melly Wardani Pratiwi; Yuliatin Nurandini; Adinda Armiyati (Mutiara Pendidikan dan Olahraga, 2026)
This study aims to descriptively analyze the ability of elementary students to imitate rhythmic gymnastics movements through the Just Dance Now application in Physical Education learning at SDN Bulay 1 Pamekasan. The background of this research stems from the low motivation and movement accuracy of students in conventional rhythmic gymnastics learning. Using a qualitative descriptive approach, this study involved 24 fifth-grade students as subjects. Data collection techniques included participatory observation, in-depth interviews, and documentation. Data were analyzed using the Miles and Huberman interactive model consisting of data reduction, data presentation, and conclusion drawing. The findings indicate that students' ability to imitate rhythmic gymnastics movements through Just Dance Now falls into the sufficient category, with students demonstrating good proficiency in basic movement patterns but experiencing challenges in complex body coordination and musical rhythm synchronization. The application successfully enhanced student enthusiasm and engagement compared to traditional methods. However, technical constraints such as internet connectivity and limited space were identified as implementation barriers. This study implies that digital game-based media like Just Dance Now can serve as an effective alternative visual aid in elementary physical education, particularly for rhythmic gymnastics instruction. Educators are encouraged to integrate technology creatively while addressing infrastructural limitations to optimize learning outcomes.